1995
DOI: 10.1152/ajpregu.1995.268.6.r1406
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-alpha acts at the preoptic hypothalamus to reduce natural killer cytotoxicity in rats

Abstract: We previously demonstrated that an intracerebroventricular injection of recombinant human interferon-alpha (rhIFN-alpha) reduced the cytotoxicity of splenic natural killer (NK) cells in rats and mice. In the present study, we investigated the brain sites at which rhIFN-alpha acts to suppress splenic NK activity in unanesthetized rats implanted unilaterally with a chronic hypothalamic cannula. A microinjection of 200 U of rhIFN-alpha into the medial part of the preoptic hypothalamus reduced NK activity to appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…For example, Sundar et al [13] reported that central IL-1 produced a marked reduction of peripheral lymphocyte activities, and that the suppressive effect was attenuated after ganglionic blockade. Similarly, the suppressive effects of foot-shock stress [22], intracranial administration of interferon-h [23], and hypothalamic stimulation [24] on splenic lymphocytes and natural killer cells are also known to be mediated through sympathetic activation. Our results are similar to these observations in that the peripheral IL-6 response induced by brain IL-1 was much depressed by ganglionic blockade, indicating a significant role for the autonomic nervous system in the response.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Sundar et al [13] reported that central IL-1 produced a marked reduction of peripheral lymphocyte activities, and that the suppressive effect was attenuated after ganglionic blockade. Similarly, the suppressive effects of foot-shock stress [22], intracranial administration of interferon-h [23], and hypothalamic stimulation [24] on splenic lymphocytes and natural killer cells are also known to be mediated through sympathetic activation. Our results are similar to these observations in that the peripheral IL-6 response induced by brain IL-1 was much depressed by ganglionic blockade, indicating a significant role for the autonomic nervous system in the response.…”
Section: Discussionmentioning
confidence: 99%
“…Again, the reduced NK cytotoxicity was abolished by pretreatment with NLTX. Furthermore, we found that the most sensitive site to microinjected IFN-· for reducing the splenic NK cytotoxicity was located in the MPO [40]. The injection of rhIFN-· at 50 and 200 U into the MPO decreased the splenic NK cytotoxicity to about 77 and 59% of the preinjection level, but no changes in NK cytotoxicity were observed after injection of rhIFN-· (200 U) into the ventromedial hypothalamus, the lateral preoptic area, the lateral hypothalamus and the paraventricular nucleus (PVN).…”
Section: Stimulation Of Central Opioid Receptors Reduces the Nk Activitymentioning
confidence: 83%
“…We focused our attention to the hypothalamo-pituitary-adrenocortical axis and the splenic innervation as potential pathways to mediate the central messages evoked by the IFN-·-CRF system. The adrenalectomy did not influence the immunosuppression after injection of rhIFN-· either into the cerebral ventricle or the MPO in the rat [27,40], suggesting that adrenal hormones do not play major roles in this immunosuppression. In fact, the main effect of IFN-· on the hypothalamo-pituitary-adrenocortical axis seems to be inhibitory [29].…”
Section: Mediation Of Ifn-·-induced Immunosuppression By the Splenic mentioning
confidence: 84%
See 1 more Smart Citation
“…We have shown that the central, but not peripheral, administration of IFN-a produces a significant suppression of splenic NK cell activity through the activation of the splenic sympathetic nerve in rats [15,16]. In addition, the action site of IFN-a to induce suppression of NK activity was the MPO [17,18], where expression of IFN-a mRNA increased on day 7 after poly I:C. It has been reported that IFN-a, but not IL-1h and TNF-a, is elevated in cerebrospinal fluid in patients with CFS [19]. Thirdly, brain 5-HT, which is suggested to be involved in the central mechanisms of the exercise-induced fatigue [9], decreased in the prefrontal cortex probably due to the IFN-a-induced over-expression of 5-HTT.…”
Section: Brain Ifn-a and Fatiguementioning
confidence: 91%